2008
DOI: 10.1002/cne.21793
|View full text |Cite
|
Sign up to set email alerts
|

Participation of μ‐opioid, GABAB, and NK1 receptors of major pain control medullary areas in pathways targeting the rat spinal cord: Implications for descending modulation of nociceptive transmission

Abstract: Several brain areas modulate pain transmission through direct projections to the spinal cord. The descending modulation is exerted by neurotransmitters acting both at spinally projecting neurons and at interneurons that target the projection neurons. We analyzed the expression of mu-opioid (MOR), gamma-aminobutyric acid GABA(B), and NK1 receptors in spinally projecting neurons of major medullary pain control areas of the rat: rostroventromedial medulla (RVM), dorsal reticular nucleus (DRt), nucleus of the soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 84 publications
(110 reference statements)
1
47
0
2
Order By: Relevance
“…Although previous extracellular unit recordings determined that SP excites a subset of RVM neurons (Budai et al 2007;Pomeroy and Behbehani 1980), these studies provided little information as to their projections and neurotransmitter content. A recent study in adult rat also determined that a majority of spinally projecting neurons express NK1 receptor immunoreactivity but did not determine the neurotransmitter content of those neurons (Pinto et al 2008). Neither whole cell recordings nor an immunohistochemical analysis identified NK1 receptors on serotonergic RVM neurons.…”
Section: Functional Nk1 Receptors Are Expressed By Nonserotonergic Spmentioning
confidence: 94%
“…Although previous extracellular unit recordings determined that SP excites a subset of RVM neurons (Budai et al 2007;Pomeroy and Behbehani 1980), these studies provided little information as to their projections and neurotransmitter content. A recent study in adult rat also determined that a majority of spinally projecting neurons express NK1 receptor immunoreactivity but did not determine the neurotransmitter content of those neurons (Pinto et al 2008). Neither whole cell recordings nor an immunohistochemical analysis identified NK1 receptors on serotonergic RVM neurons.…”
Section: Functional Nk1 Receptors Are Expressed By Nonserotonergic Spmentioning
confidence: 94%
“…morphine), which mainly target MORs, remain the most powerful analgesics available for pain relief [14,15,16,17,18,19]. Previous studies showed that MORs and β-endorphin-sensitive opioid receptors have been expressed in the dorsal root ganglia neurons and the superficial dorsal horn of the spinal cord [20,21,22]. Many experiments have proven that opioid receptors are involved in the modulation of nociceptive afferent transmission and opioid analgesia at the spinal cord [18,19,23].…”
Section: Discussionmentioning
confidence: 99%
“…SP and NK-1 receptors have been identified in the RVM (Budai et al 2007;Marson and Loewy 1985;Saffroy et al 1988Saffroy et al , 2003, and nearly half of the NK-1-expressing neurons from RVM project to the dorsal horn of the spinal cord (Pinto et al 2008). Dickenson and colleagues originally proposed a pathway through which excitation of NK-1-expressing neurons in the superficial spinal dorsal horn leads to descending facilitation (Suzuki et al 2002) via serotonin and 5-HT 3 receptors in the spinal cord (Suzuki et al 2004a(Suzuki et al , 2004b; see also Lagraize et al 2010).…”
Section: Neurotransmitters Involved In Descending Facilitationmentioning
confidence: 99%